The OsGAPC3 mutation significantly affects grain quality traits and improves the nutritional quality of rice - Peng, Bo; Liu, Yan; Sun, Xiaoyu; Zhao, Qiang; Qiu, Jing; Tian, Xiayu; Peng, Jing; Zhang, Zhiguo; Wang, Yujian; Huang, Yaqin; Pang, Ruihua; Zhou, Wei; et al. (Frontiers in Plant Science, 2024)
The glycolytic enzyme cytoplasmic glyceraldehyde-3-phosphate dehydrogenase (GAPC3) is involved in multiple biological processes in plants, including transcriptional regulation, and material metabolism. However, the relationship between OsGAPC3 and the quality traits of rice is poorly understood. Here we identify OsGAPC3 mutations that enhance the protein content and grain nutritional quality of rice by regulating the OsAAP6 gene expression. The number and volume of type-II protein bodies in the endosperm of the OsGAPC3 mutants, and GPC increase significantly. We report significant increases in chalkiness area and degree, and decreases for starch content, gel consistency, and taste value. Results of proteomic detection and analysis reveal that OsGAPC3 affects the major storage substances (proteins and starch) metabolism in rice, and the accumulation of proteins and starch in the endosperm. Additionally, the OsGAPC3 mutation significantly decreases the rice-seedling salt tolerance. Therefore, OsGAPC3 affects multiple quality traits of rice, participates in regulating rice-seedling salt-stress response. These data can be used to design better-quality and stronger salt-resistant rice varieties.